Three-Dimensional Measures of Bony Resection During Femoral Osteochondroplasty Are Related to Alpha Angle Measures: A Cadaveric Study - Thomas D. Alter, M.S.; Philip Malloy, Ph.D., P.T.; Alex C. Newhouse, B.S.; Sunikom Suppauksorn, M.D.; Alejandro Espinzoa Orias, Ph.D.; Jorge Chahla, M.D., Ph.D.; Nozomu Inoue, M.D., Ph.D.; Shane J. Nho, M.D., M.S. (Arthroscopy, Sports Medicine, and Rehabilitation, 2021)
Purpose: To determine whether 3-dimensional (3D)–reconstructed proximal femoral bone models can be used to quantify femoral osteochondroplasty and to determine whether the 3D-based metrics are related to clinical alpha angle measures. Methods: Six cadaveric specimens with cam-type morphology underwent open femoral osteochondroplasty. Alpha angles were measured on the oblique axial computed tomography slice before and after femoral osteochondroplasty. Preoperative and postoperative computed tomography–based 3D reconstructed femur models were generated for each cadaveric specimen. A 3D-3D registration technique was used to merge the preoperative and postoperative models to measure the surface-to-surface distance between the model surfaces. Bivariate correlation analyses were used to determine the correlations between the preoperative, and the difference between the preoperative and postoperative alpha angle (Δ alpha angle) measures and each of the femoral osteochondroplasty variables of surface area (mm2), volume (mm3), maximum height (mm), and mean height (mm). The strength of the bivariate correlations was defined as follows: weak 0.1 to 0.3, moderate 0.3 to 0.5, and strong as 0.5 to 1.00. Results: Bivariate correlations revealed a strong positive correlation between preoperative alpha angle with femoral osteochondroplasty volume (r = 0.899, P = .007) and surface area (r = 0.899, P = .007). No significant correlations were found between the change in alpha angle and the osteochondroplasty variables. Conclusions: In this study, pre- and postoperative 3D bone models could be used to quantify femoral osteochondroplasty and to determine if the 3D-based metrics are related to clinical alpha angle measures. Clinical Relevance: 3D-reconstructed image bone models may be helpful to ensure that adequate femoroplasty is performed intraoperatively, in particular with arthroscopic approach in which visualization may be challenging due to capsular management issues and surgeon experience.